2022
DOI: 10.18280/ijht.400122
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Performance of Spiral Flat Plate Solar Water Collector

Abstract: Water stream flow is the major factor that affects the performance of a spiral solar water collector, it can be maximize the collector performance by decreasing the water stream flow velocity. The water stream flow was in two spiral tube arrangements of length 15 m, diameter 0.012 m, and number of coils (11). The inner surface of the solar collector was coated with matte black paint with a mixture of nanomaterial (thermal dye with 5% TiN). The experimental rig placed in Babylon - Iraq, at longitude (44.4 E) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…The results indicated that the maximum temperature difference for the experimental case is (15 K) and (38 K) for theoretical results. These results of the current SSC give a temperature difference more than that obtained in reference [9] which was (12.3 K) under similar weather conditions. In addition, the spiral tube length in their study [9] is longer with an increase of (1.5 m) compared with current work and extra five coil turns.…”
Section: Open Systemsupporting
confidence: 57%
See 2 more Smart Citations
“…The results indicated that the maximum temperature difference for the experimental case is (15 K) and (38 K) for theoretical results. These results of the current SSC give a temperature difference more than that obtained in reference [9] which was (12.3 K) under similar weather conditions. In addition, the spiral tube length in their study [9] is longer with an increase of (1.5 m) compared with current work and extra five coil turns.…”
Section: Open Systemsupporting
confidence: 57%
“…These results of the current SSC give a temperature difference more than that obtained in reference [9] which was (12.3 K) under similar weather conditions. In addition, the spiral tube length in their study [9] is longer with an increase of (1.5 m) compared with current work and extra five coil turns. For the daily time from 11:00 to 14:30, the water mass flow rate increases up to (0.075 kg/s).…”
Section: Open Systemsupporting
confidence: 57%
See 1 more Smart Citation